The Role of Mosque Management in Optimizing The Function of The Mosque As A Center of Worship, (Case Study on The Management of Sholihin, Tangkil, Manang, Grogol, Sukoharjokan Mosques) - Sarwan Uya; Yetty Faridatul Ulfah; Sukari Sukari (Return : Study of Management, Economic and Bussines, 2023)
The purpose of this study is to find out: 1). The role of management at Sholihin Mosque, Tangkil, Manang, Grogol, Sukoharjo is a process to prosper the mosque and the role of management at Sholihin Tangkil Mosque is also to optimize all mosque activities and activities. 2). Optimization of the function of the mosque as a center of worship at Sholihin, Tangkil, Grogol, Sukoharjo Mosques, namely by maximizing all aspects of activities, infrastructure and facilities to provide comfort in worship (five daily prayers) in the mosque and centralizing da'wah and social activities at the Sholihin Tangkil Mosque. 3). Obstacles to mosque management in optimizing the function of the mosque as a center of worship at Sholihin, Tangkil, Grogol, Sukoharjo Mosques are busy mosque administrators with their responsibilities outside the Sholihin Tangkil Mosque. This research method uses qualitative research methods. Qualitative research is a type of research that produces findings that cannot be achieved using statistical procedures or other means of quantification. The techniques used by researchers in collecting data on qualitative research methods are carried out in natural settings, both through observation, interviews and documentation. While the place of research is at Sholihin Tangkil Mosque, Manang, Grogol, Sukoharjo. The results of this study show that: 1). The role of management at Sholihin Tangkil Mosque, Manang, Grogol, Sukoharjo has implemented its role starting from planning, organizing, mobilizing and supervising. 2). Optimization of the function of the mosque as a center of worship at Sholihin, Tangkil, Grogol, Sukoharjo Mosques by maximizing all activities, activities and programs of the mosque. 3). The constraints of mosque management in optimizing the function of the mosque as a center of worship at Sholihin, Tangkil, Grogol, Sukoharjo Mosques are certainly inseparable from obstacles or things that can be obstacles in the optimization process, namely the busyness of takmir administrators, the financial crisis of mosques and disruptions in worship.